MODAL SPIRITUAL, MOTIVASI, BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI PENGARUHNYA TERHADAP KEPUASAN KERJA KARYAWAN YAYASAN SAHABAT YATIM INDONESIA - Fathia Zahrah; Hemmy Fauzan (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2022)
This study aims to see how the influence of spiritual capital, motivation, organizational culture and organizational commitment on employee job satisfaction with Yayasan Sahabat Yatim Indonesia as its research object. Quantitative testing was used in this study, while the sample used was 82 respondents who were employees of the Yayasan Sahabat Yatim Indonesia. The sampling form used was non-probability sampling with a purposive sampling technique. Multiple linear regression is used in analyzing the data. The results of multiple linear regression give the following results: 1. Spiritual Capital has a significant positive effect on Job Satisfaction, 2. Motivation has a significant positive effect on Job Satisfaction, 3. Organizational Culture has a significant positive effect on Job Satisfaction, 4. Organizational Commitment has a positive effect significantly on Job Satisfaction, and 5. Spiritual Capital, Motivation, Organizational Culture, and Organizational Commitment together have a simultaneous effect on Job Satisfaction of Indonesian Yatim Friends Foundation employees.